Hyperglycemia in Turner syndrome: Impact, mechanisms, and areas for future research - Mitsch, Cameron; Alexandrou, Eirene; Norris, Andrew W.; Pinnaro, Catherina T. (Frontiers in Endocrinology, 2023)
Turner syndrome (TS) is a common chromosomal disorder resulting from complete or partial absence of the second sex chromosome. Hyperglycemia, ranging from impaired glucose tolerance (IGT) to diabetes mellitus (DM), is common in TS. DM in individuals with TS is associated with an 11-fold excess in mortality. The reasons for the high prevalence of hyperglycemia in TS are not well understood even though this aspect of TS was initially reported almost 60 years ago. Karyotype, as a proxy for X chromosome (Xchr) gene dosage, has been associated with DM risk in TS – however, no specific Xchr genes or loci have been implicated in the TS hyperglycemia phenotype. The molecular genetic study of TS-related phenotypes is hampered by inability to design analyses based on familial segregation, as TS is a non-heritable genetic disorder. Mechanistic studies are confounded by a lack of adequate TS animal models, small and heterogenous study populations, and the use of medications that alter carbohydrate metabolism in the management of TS. This review summarizes and assesses existing data related to the physiological and genetic mechanisms hypothesized to underlie hyperglycemia in TS, concluding that insulin deficiency is an early defect intrinsic to TS that results in hyperglycemia. Diagnostic criteria and therapeutic options for treatment of hyperglycemia in TS are presented, while emphasizing the pitfalls and complexities of studying glucose metabolism and diagnosing hyperglycemia in the TS population.